(untitled) (Spectrum of Humanities and Social Sciences, 2025)
This paper critically reviews the cooperative movement in Nepal, focusing on its main issues and solutions. The cooperative movement in Nepal has played a vital role in promoting socio-economic development, especially in rural areas. It has empowered communities by providing access to finance, creating employment opportunities, and fostering social inclusion. However, despite its contributions, the cooperative sector faces several critical challenges. This paper uses the secondary sources of data from cooperative reports, official documents, related research articles of journals, which have been minutely reviewed. This is qualitative analysis identifies the weak governance, political interference, lack of proper regulation, limited access to technology, inadequate financial literacy among members, and mismanagement of funds as the major challenges. In addition, the unchecked propagation of cooperatives has highlighted critical vulnerabilities in their transparency and accountability. Mitigating these risks necessitates a multi-faceted approach, including policy reform, robust regulatory oversight, strategic capacity-building, digital transformation, and improved financial literacy.